Pigment epithelium-derived factor may induce antidepressant phenotypes in mice by the prefrontal cortex. (6th February 2022) - Bai, Mengge; Yu, Heming; Chen, Chong; Xu, Xingzhe; He, Yong; Wang, Yue; Tian, Yu; Wu, Zhonghao; Lan, Tianlan; Li, Yan; Chen, Xiangyu; Chen, Zhi; et al.
Highlights: The level of PEDF is down-regulated in the prefrontal cortex of CUMS and CSDS models. Overexpression of PEDF in the prefrontal cortex induces antidepression-like behaviors. PEDF exerts antidepressant effects on the tryptophane and glutamate in the PFC. Abstract: Pigment epithelium-derived factor (PEDF) is a multifunctional glycoprotein encoded by SERPINF1 and our previous study reported that PEDF may have antidepressant effects. As a key brain region regulating cognition, memory and emotion, the prefrontal cortex (PFC) has been studied extensively in major depressive disorder (MDD), but there are few reports on the relationship between PEDF and the PFC. In this study, enzyme-linked immunosorbent assay showed that the PEDF level was decreased in the plasma of MDD patients compared with that of healthy controls. Western blotting validated that the PEDF expression in the PFC was downregulated in the mouse chronic social defeat stress and rat chronic unpredictable mild stress models of depression. Correspondingly, normal mice overexpressing PEDF in the PFC showed depression-resistant phenotypes. We detected PFC metabolite levels by liquid chromatography-tandem mass spectrometry and found significant upregulation of 5-hydroxyindoleacetic acid, kynurenine, 5-hydroxytryptamine, ornithine and glutamine, and downregulation of 5-hydroxytryptophan, glutamic acid and aspartic acid in PEDF-overexpressing mice compared with control mice, in which no such changes were detected. Combined with the above findings, this provides an insight into a potential mechanism of the antidepressant effects of PEDF via the PFC, which may help to improve understanding of depression pathophysiology.